Whole genome sequencing of clinical strains of Mycobacterium tuberculosis from Mumbai, India: A potential tool for determining drug-resistance and strain lineage. (December 2017) - Chatterjee, Anirvan; Nilgiriwala, Kayzad; Saranath, Dhananjaya; Rodrigues, Camilla; Mistry, Nerges
Abstract: Amplification of drug resistance in Mycobacterium tuberculosis ( M.tb ) and its transmission are significant barriers in controlling tuberculosis (TB) globally. Diagnostic inaccuracies and delays impede appropriate drug administration, which exacerbates primary and secondary drug resistance. Increasing affordability of whole genome sequencing (WGS) and exhaustive cataloguing of drug resistance mutations is poised to revolutionise TB diagnostics and facilitate personalized drug therapy. However, application of WGS for diagnostics in high endemic areas is yet to be demonstrated. We report WGS of 74 clinical TB isolates from Mumbai, India, characterising genotypic drug resistance to first- and second-line anti-TB drugs. A concordance analysis between phenotypic and genotypic drug susceptibility of a subset of 29 isolates and the sensitivity of resistance prediction to the 4 drugs was calculated, viz. isoniazid-100%, rifampicin-100%, ethambutol-100% and streptomycin-85%. The whole genome based phylogeny showed almost equal proportion of East Asian (27/74) and Central Asian (25/74) strains. Interestingly we also found a clonal group of 9 isolates, of which 7 patients were found to be from the same geographical location and accessed the same health post. This provides the first evidence of epidemiological linkage for tracking TB transmission in India, an approach which has the potential to significantly improve chances of End-TB goals. Finally, the use of Mykrobe Predictor, as a standalone drug resistance and strain typing tool, requiring just few minutes to analyse raw WGS data into tabulated results, implies the rapid clinical applicability of WGS based TB diagnosis.